Soil micromorphology : a basic and applied science - International Working-Meeting on Soil Micromorphology 1988 : San Antonio, Tex.); Douglas, Lowell A.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1990)
The book includes selected papers from those presented at the International Working Meeting on Soil Micromorphology in San Antonio, Texas, July 1988. Each section of the book is introduced with an invited plenary paper followed by selected contributed manuscripts. The volume is intended to give the reader insight into the more recent research work involving soil micromorphology and an evaluation of the present day state of the science. New applications of micromorphology to both lunar pedology and archeology are presented. Recently developed methods for staining of microorganisms and thin section fluorescence microscopy are presented. The volume presents a summary of the research findings of the major practitioners of soil morphology and will give the reader insight as to the present state of the discipline. New methods and techniques will be made available to the reader. The book is intended for students, practicing micromorphologists, soil scientists, geologists, and geomorphologists.
Preface (L.P. Wilding). Applications to Agronomic Sciences. Applications to Pedology. Hydromorphic Solis. Soil with Gypsum or Carbonate. Applications to Archaeology. Lunar Pedology. Weathering and Neoformation. Methods. Applications to Paleopedology. Terminology.
"Proceedings of the VIIIth International Working Meeting of Soil Micromorphology, San Antonio, Texas, July 1988."
"Sub-commission of Soil Micromorphology of International Society of Soil Science."
Includes bibliographical references.
Print version record.
Elsevier
Keywords: Soil micromorphology -- Congresses; Sols -- Micromorphologie -- Congrès.; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Soil Science; Soil micromorphology; Micromorfologie; Bodem; Soils -- Micromorphology; Electronic books